Trade liberalization and SO2 emissions: Firm-level evidence from China's WTO entry - Lei Li; Andreas Löschel; Jiansuo Pei; Bodo Sturm; Anqi Yu (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
Is trade liberalization contributing to cleaner production amongst manufacturing firms? Theoretical predictions and empirical evidences are mixed. This study utilizes China's dual trade regime and China's WTO entry in 2001 to construct a unique micro dataset on manufacturing firms for China for the period 2000-2007, and performs a difference-in-difference estimation strategy to directly examine this issue. Specifically, normal exporters that saw tariff changes during the same period form the treatment group; while processing exporters that enjoy tariff-exemptions both pre- and post-WTO entry serve as the control group. Results show that China's WTO entry contributed to a lower SO2 emission intensity for normal exporting firms. We further examine the mechanism and show that the productivity channel accounted for the observed pattern. Specifically, more efficient normal exporters saw greater decline of SO2 emission intensity than average normal exporters. This study contributes to a better understanding of the impact of trade on the environment, especially in developing countries. It also complements the literature in terms of providing China's micro evidence on the impact of trade liberalization on firm's environmental performance.
Keywords: F18; Q53; Q56; 330; WTO; trade liberalization; dual trade regime; SO2 emission intensity; China